Mehmet Hıfzı Özcan in Terms of Biographic Sociology - Meltem Işık Afacan (Journal of Educational Issues, 2024)
Research based on life story is based on seeing from the perspective of the person being researched and revealing the social structure and processes that make up this perspective (Yildirim, 1999). For this reason, studies based on biographical sociology are one of the most appropriate qualitative studies in terms of explaining the life story of the researched person. Disability is a condition in which a person cannot fully perform certain movements, senses, or functions due to a physical or mental disorder that occurs at birth or later. Many scientists have done various studies on this situation. One of them is the founder and Honorary President of Turkish Spastic Children Foundation (TSCV), Prof. Mehmet Hıfzı Özcan. Özcan, who is a professor of neurology, has contributed to the better recognition and solutions of spastic children, especially disabled people and their problems in Türkiye. The life, Works and contributions of Özcan, who is one of the names who construct the infrastructure of the current situation of disability with the books he wrote and the thoughts he put forward, are discussed in this research. Thus, it is aimed that Mehmet Hıfzı Özcan, who has contributed to the participation of Türkiye in the Special Olympic Games, will be better known in our sports culture.